The Relationship Between the Role of Madrasah Heads, Work Motivation, and Professional Competence with the Performance of State Madrasah Tsanawiyah Teachers - Faiza, Dwi Eni Nur Faiza; Supriyanto, Ahmad; Sunandar, Asep (PT. BATARI EDU CALYA, 2024)
This study aims to analyse: (1) the relationship between the role of the principal of religious school in Malang County and teachers' performance in MD as agreed by teachers respectively; machine translation teachers in Malang County relationship; (3) there is a relationship between the ability and performance of national machine translation teachers in Malang City; and the performance of machine translation teachers in the social network of Malang County. This study used various descriptive and correlational analysis methods to determine the relationship between the variables. The results of this research show that: (1) The role of religious school has a positive relationship with the achievement of teachers and sig scores. If equal to 0.000 < 0.05, the calculated r value is 0.323 > r table is 0.146; If equal to 0.000 < 0.05, the calculated r value is 0.713 > r table is 0.146; If equal to 0.000 < 0.05, the calculated r value is 0.812> r table is 0.146; (4) The role of the religious school principal, support work and ability are related to the success of teachers and SIG scores. 0.000 < 0.05, the strength of the relationship is 0.829, which means the relationship is in the excellent category